Accumulation and Circulation of the Knowledge Needed for Biotech Business Promotion by Engineers of R&D Section in an IT Enterprise: The Case of Hitachi Software Engineering Co., Ltd - Ota, Hirofumi; Motohashi, Kazuyuki (School of Business and Management Institut Teknologi Bandung, 2011)
Much research has been carried out on the accumulation and effective use of knowledge as a company-specific form of intellectual property. However, insufficient attention has been given to research focusing on the effects of micro-level knowledge absorption and its effective use. In this paper, we try to demonstrate what should be done in order to promote new biotech business from the perspective of each engineer’s knowledge, through a micro-level investigation focusing on the life science business section of one IT enterprise. Based on the results of a questionnaire survey of engineers, interviews of several engineers, and patent data analysis, we discuss the progress of the biotech business in an IT enterprise from the aspect of accumulation and circulation of knowledge in a core technology field, the IT business, and a technology field of new entry, the biotech business. This paper reports that the positive growth cycle of biotech business promotion in an IT enterprise, using Hitachi Software Engineering Co., Ltd. as a case, attained by incorporating the latest biotech knowledge from junior engineers and utilizing IT knowledge from middle engineers leads to the recruiting of qualified students.Keywords: accumulation and circulation of the knowledge, biotech business, open innovation, patent data analysis, questionnaire survey